Economic development and the patterns of manufactured exports - Ranadev Banerji; Juergen B. Donges (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1972)
The need to expand the export of manufactures from less developed countries has now been realised by national and international bodies. To device meaningful policies, it seems necessary to understand whether and how the share of manufactures in a country's total exports is related to certain supply-oriented characteristics. For this purpose, a multiple regression analysis on the basis of cross-sectional data is attempted in this study . In a pooled sample of developed and developing countries, the share of manufactures in total exports is positively associated not only with the level of per capita income and the degree of industrialisation , but also with the density and size of population and ( though not statistically significant ) the availability of skills . All these variables together explain statistically more than 60 per cent of the total variation in observed data on the share of manufactures in total exports. The share of manufactures in total exports is likely to increase rapidly with per capita income, but only up to a certain point after which it levels off. Countries with a high density of population tend to export manufactures at an earlier stage and in greater proportion than countries with a low density. For most of the developed countries the actual shares of industrial exports are seen to have exceeded the "expected" shares, whereas for most of the less developed countries the reverse holds true . When the cross-section analysis is confined to less developed countries only, the share of manufactures in total exports, although positively associated with the degree of industrialisation , is conversely ( but not significantly ) related to per capita income.
Keywords: 330